Aggressiveness of Phytophthora cinnamomi in avocado seedlings and effect of pathogen inoculum concentration and substrate flooding periods on root rot and development of the plants - Fischer, Ivan Herman; Sampaio, Aloisio Costa [UNESP]; Almeida Bertani, Rosemary Marques de; Leite Goncalves, Bruno Henrique; Feichtenberger, Eduardo (Soc Brasileira Fruticultura, 2020)
The present study evaluated the aggressiveness of Phytophthora cinnamomi isolates and the effect of pathogen inoculum concentration and periods of substrate flooding on root rot and plant development. Twelve pathogen isolates were inoculated on the collar region of avocado seedlings with or without wounding. Only 31.3% of the inoculated plants without wounding developed lesions, compared to 100% of the plants with wounding, while the isolates showed different aggressiveness levels. Avocado seedlings had their substrate inoculated with 0, 0.1% and 1.0% (m/v) wheat seeds colonized by the pathogen per pot, and four periods of 0, 12 and 24 h substrate flooding were produced at fortnightly intervals. The assessed parameters were number of leaves per plant, collar diameter, plant height, leaf area index, visual severity percentage of infected roots, fresh mass (%) of diseased roots and dry mass of shoot and roots. Both pathogen inoculation and substrate flooding caused root rot; however, combination of these two factors produced an additional effect on disease symptoms. Root rot severity was superior to 50% when soilless substrate had 0.1% (m/v)P cinnamomi inoculum and flooded for 12-24 h after inoculation, conditions that can be recommended for pathogenicity and disease control studies using potted avocado plants.
Keywords: Persea americana; root disease; soil flooding